EFL TEACHER'S PEDAGOGICAL BELIEFS IN TEACHING AT AN INDONESIAN UNIVERSITY - Diah Safithri Armin; Ayu Meita Puteri Siregar (JURNAL TARBIYAH, 2021)
Teachers should have pedagogical beliefs in their studies, which function as a filter and guidance for their decision-making and teaching methods in the teaching-learning process. To promote an active and meaningful learning experience, Indonesian curriculum policy incorporated principles that place students at the center of the learning process. However, most of the time, teachers are in charge of the teaching-learning process and become the center of the learning process, while students are passive recipients of knowledge.This study was conducted to find out teachers' pedagogical beliefs in teaching at university. The present study was a basic interpretative qualitative study with five English teachers as the participants, and the data were collected through observation, questionnaire, and field notes. The data were analysed by data reduction, data display, and concluding. The study results showed that the teachers believed that teaching is the process of transmitting and constructing knowledge. This study implied that the EFL teachers believed and implemented a student-centered approach in the teaching-learning process.